The Common Science Misconceptions in Indonesia Junior High School Students - Putri Anjarsari (Universitas Negeri Yogyakarta, 2018)
Identifying and correcting the mistake that students make about science concept is very important. The main purpose of this article is to analyse some publications about common science misconceptions in some science topics in junior high schools. Misconceptions are erroneous perceptions of what is universally accepted. The misconception identification in this research is based on the descriptive research using some journal publications in Indonesia university which is held science education study program. Study found that : the concept of photosynthesis, respirations, the relationship of photosynthesis and respirations, force (action and reaction forces) , and Newton laws are most frequently investigated as misconceptions of science. Students’ interest and learning environments are some reasons of students’ misconceptions.